Stochastic processes drive the dynamic assembly of bacterial communities in Salix matsudana afforested soils - Wang, Can; Masoudi, Abolfazl; Wang, Min; Wang, Yin; Zhang, Ze; Cao, Jingkun; Feng, Jian; Yu, Zhijun; Liu, Jingze (Frontiers in Microbiology, 2024)
This study provides critical insights into the dynamic shifts in soil bacterial communities within an ecosystem transitioning from agricultural land to afforested regions, specifically under Salix matsudana. By employing high-throughput sequencing across three distinct months, we uncover significant temporal variability in bacterial diversity and community structures, which are closely tied to fluctuations in temperature and precipitation. Our findings reveal the abundance of the dominant bacterial phyla, such as Actinobacteria and Proteobacteria did not change significantly, highlighting the stability and resilience of the microbial community across seasonal transitions. Notably, the increasing similarity in community composition from August to October indicates a reduction in species turnover, likely driven by more homogeneous environmental conditions. Through comprehensive network analysis, we identify the pivotal role of keystone species, particularly the human pathogen Nocardia, in maintaining community stability under reduced soil moisture. The observed variations in community connectivity underscore the microbial community's resilience and adaptability to seasonal shifts, with higher stability in August and October contrasting with the instability observed in September. These results underscore the complex interplay between stochastic and deterministic processes in bacterial community assembly, significantly shaped by prevailing environmental conditions.The insights gained from this research have far-reaching implications for forestry management and conservation strategies, particularly in regions undergoing similar afforestation efforts.